FUSION PLASMA NUCLEAR-PHYSICAL DIAGNOSTICS METHODS - Zhusupov, M.A.; Kabatayeva, R.S. (Recent Contributions to Physics, 2009)
In the article -plasma ion component nuclear-physical diagnostics problems by lithium isotopes injection are considered. Cross sections’ resonance structure of reactions on and nuclei is determined by the structural peculiarities of the excited states of and nuclei, which have low values of -widths. Average rates and -quanta yield for the reactions have been calculated.